IMPLEMENTATION OF E-GOVERNMENT THROUGH APDS APPLICATION TO IMPROVE REGIONAL TAX SERVICES: A CASE STUDY OF BPPD SIDOARJO - Nabilah, Helmina Lingga; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the Sidoarjo Regional Tax Application (APDS) as a digital innovation designed to improve the efficiency and effectiveness of local tax services. Method: A qualitative research approach was adopted through interviews, observations, and document analysis involving staff from the Sidoarjo Regional Tax Service Agency (BPPD) and users of the application. The data were analyzed descriptively to identify key success factors and challenges during implementation. Results: The findings indicate that APDS enhances administrative efficiency, promotes transparency, and reduces bureaucratic barriers to tax collection. The success of this innovation is attributed to organizational support for digitalization, employee adaptability, and active community participation in utilizing the application. Novelty: This study provides new insights by demonstrating that the success of digital tax service innovation depends not only on technological readiness but also on organizational adaptability and staff commitment. The results contribute to the broader discourse on digital governance and offer a replicable model for local governments seeking to reform bureaucratic systems through digital transformation.